University teachers’ perception of assessment in Kazakhstan - Makhmetova, Zhadyra (Nazarbayev University Graduate School of Education, 2014)
Assessment is an integral part of teaching and learning. There have been many research studies worldwide conducted on assessment, and specifically focusing on assessment in higher education. Many international research studies focus on the importance of teachers' assessment beliefs and practices. However, this topic has not been researched in Kazakhstan. The purpose of this qualitative study is to explore teachers‟ assessment beliefs and practices of assessment approaches in one university in Oral town of Kazakhstan. The case study design was conducted, and it enabled the researcher to undertake an in-depth exploration of the topic in one university in Oral. Purposefully selected five university teachers were interviewed, and teachers‟ syllabuses were reviewed to gather data. The study thus presents interesting findings about the university teachers‟ assessment beliefs and practices. The findings contribute to the body of knowledge in this field and also offer some key practice and policy implications
Keywords: university teachers' assessment; educational system; Graduate School of Education; assessment of learning; teachers‟ assessment beliefs and practices; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education